(untitled) (IIUC Business Review, 2022)
This paper, through a mixed-method approach (interview and survey questionnaire), investigates the responsibility of family towards teaching ethics and morality to children for sustainable development, specifically in Bangladesh. Reports and studies have shown that children have shown unethical and immorality practices due to a lack of education about Ethics and Morality, similar to those of tertiary-level graduates. This situation becomes an impediment to sustainable development. Malpractices, unethical behavior, and immorality actions are rampant reported in the mainstream news. Eventually, such a situation leads to non-sustainable development. The findings opined that the family has a fiduciary responsibility to teach Ethics and Morality to children. The respondents contended that the value-driven approach through the Tawhidic Paradigm (Unity of God) of teaching ethics and morality empowered society in Bangladesh with high ethical and moral conducts in decisions and actions. This study provides practical implications for policymakers and practitioners for socio-economic policies and practices in Bangladesh for sustainable development. The results of the study are contextually limited by the size of the samples, area, and robustness of the analysis. IIUC Business Review Vol. 7-8, Dec. 2018-19 pp. 31-46